24x6 + 12x4 + 15x2 factor the greatest common factor, 3x2 = 3x2(8x4 + 4x2 + 5)
16? using 16, you have (3x2 + 4)(3x2 + 4) = 9x2 + 24x + 16
if you rearrange it, it becomes 4y + 8 = 3x2 -2x +1 4y = 3x2 -2x -7 y= (3x2 -2x -7)/4 which is a parabola
A polynomial is an expression of various exponentials of a variable wich may or may nor have coefficients and constants. The coefficients may have a radical, square root, cube root etc, but not the variable. A radical expression is any expression involving square roots, cube roots, etc. These may have the variable inside the radical but do not have to have them. sq root (5) is a radical expression, so is sq root (x) 3x2 + 2x - 9 is a polynomial, so is x + sq root (5)
(3x+5)(x-2) x=2 x=-5/3 you separate it into two brackets like above. as you see -2 and 5 times to -10 3x and x times to make 3x2 3x and -2 times to make -6x x and 5 time to make 5x add them all together and you should get: 3x2 -x -10 you have to work back or you can use the quadratic formula where: ax2 + bx + c =0 or you can also complete the square, but i can't do that srry.
This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========
3x2 + 6x is ONE expression. A common factor is a factor that is COMMON to two (or more) expressions - not just one. An alternative answer: 3x can be factored out of both of those.
3x2 + 27x +60
3x2(x2 - 3)
-8x + 3x2 - 3
3x2 + 9x 3x(x + 3) -------------
It is an expression that can be simplified to: 4x2-42
(3x + 1)(x + 5)
x2(x + 3)
It is 4 terms of an algebraic expression.
All terms include 3x2. So we can factor the expression as :- 3x6 + 54x4 + 243x2 = 3x2(x4 + 18x2 + 81) And (x4 + 18x2 + 81) = (x2 + 9)2 Putting the two parts together gives, 3x2(x2 + 9)2.
(3x - 5)(x + 3)